2014
DOI: 10.1523/jneurosci.3655-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dose-Dependent Impact of D1 Receptor Activation on Motor Cortex Plasticity in Humans

Abstract: The neuromodulator dopamine plays an important role in synaptic plasticity. The effects are determined by receptor subtype specificity, concentration level, and the kind of neuroplasticity induced. D1-like receptors have been proposed to be involved in cognitive processes via their impact on plasticity. Cognitive studies in humans and animals revealed a dosage-dependent effect of D1-like receptor activation on task performance. In humans, D1-like receptor activation re-establishes plasticity under D2 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 57 publications
4
63
1
1
Order By: Relevance
“…This might be explained by the activation of different 5-HT receptor subtypes, the concentration of 5-HT agonists and antagonists, and different brain sites of action (Mori et al, 2001;Staubli and Otaky, 1994). To explore the reasons for these inconsistent results and to learn more about the impact of serotonin on neuroplasticity in humans, future studies should consider specific serotonergic receptor subtypes, apply different 5-HT-receptor agonists and antagonists, and explore the impact of different dosages, which might be a relevant factor for the strength and direction of effects, as seen for other neuromodulators, which have nonlinear effects on plasticity (Frensnoza et al, 2014;Monte-Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the activation of different 5-HT receptor subtypes, the concentration of 5-HT agonists and antagonists, and different brain sites of action (Mori et al, 2001;Staubli and Otaky, 1994). To explore the reasons for these inconsistent results and to learn more about the impact of serotonin on neuroplasticity in humans, future studies should consider specific serotonergic receptor subtypes, apply different 5-HT-receptor agonists and antagonists, and explore the impact of different dosages, which might be a relevant factor for the strength and direction of effects, as seen for other neuromodulators, which have nonlinear effects on plasticity (Frensnoza et al, 2014;Monte-Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Low (25 mg) and high (200 mg) doses of L-Dopa abolished anodal tDCS-induced LTP-like plasticity (Monte-Silva et al, 2010), and even turned PASinduced LTP-like plasticity into LTD-like plasticity (Thirugnanasambandam et al, 2011b). These effects were largely reproduced by selective stimulation of D1Rs (Fresnoza et al, 2014) or D2Rs (Monte-Silva et al, 2009). In contrast, a medium (Thirugnanasambandam et al, 2011b).…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…In contrast, a medium (Thirugnanasambandam et al, 2011b). These effects of a medium L-Dopa dose may depend on the balance of D1R-and D2R-stimulation as selective stimulation of either receptor produces different effects (Fresnoza et al, 2014;Monte-Silva et al, 2009). In addition, data suggested that the modulatory effects of dopamine depend on the NIBS protocol applied.…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…Cohens' d and effect size r for paired t tests effects of nicotine cannot be ruled out and were not explicitly surveyed so far but are known for neuromodulators like dopamine(Fresnoza et al 2014;Monte-Silva et al 2011).…”
mentioning
confidence: 99%